Analisa Dan Perancangan Sistem Informasi Pelayanan Desa Berbasis Web Menggunakan Standar Iso/Iec 25010 - Fiqih Zulfikar; Wahyu Andriyano; Chairul Anwar (PT Jurnal Cendekia Indonesia, 2026)
This study aims to evaluate and design an online-based village service information system as an effort to improve the effectiveness and quality of services for residents. The main problems identified include administrative processes that are still carried out manually, slow data processing, and a lack of information transparency. The approach used in this study includes requirement analysis through observation and interviews, system design using modeling tools such as Use Case Diagrams, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD), as well as web-based system implementation. System quality testing is conducted based on the ISO/IEC 25010 standard, focusing on functional suitability, usability, and performance efficiency through questionnaires and direct testing. The findings indicate that the developed system is able to streamline administrative service processes, accelerate data processing, and provide more transparent and accessible information for residents, making it an efficient solution to improve the quality of public services at the village level.